Safety and Technical Performance of Bilateral Decubitus CT Myelography using Standard versus Increased Intrathecal Iodinated Contrast Volume - Edelmuth, Diogo G.L.; Leão, Renata V.; Filho, Eduardo N.K.; Souza, Marcio N.P.; Calderaro, Marcelo; Kranz, Peter G. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Lateral decubitus CT myelography (LDCTM) is one of the main studies for the detection of CSF-venous fistulas, but detection of CSF-venous fistulas is dependent on intrathecal contrast attenuation. The purpose of this investigation was to assess the tolerability and technical performance of increased intrathecal doses of myelographic contrast compared with standard doses.MATERIALS AND METHODS: This is a retrospective series of 24 patients who underwent LDCTM following administration of either 10 or 20 mL of intrathecal iodinated contrast media (300 or 320 mg/mL of iodine content). Patients were scanned in the initial lateral decubitus position and then turned to the contralateral side and re-scanned in the same session. The safety and tolerability of the 20 mL dose was assessed from clinical records. The technical performance of the studies was compared between groups (10 or 20 mL) by measuring attenuation values over the lateral thecal sac at standardized levels. Both the initial scan and the scan after turning the patient to the contralateral side were assessed.RESULTS: No moderate or severe adverse event was recorded in either group. The 20-mL group showed higher attenuation values, which were statistically greater on the second side examined compared with the standard-dose group.CONCLUSIONS: Increased volume of intrathecal contrast was well-tolerated and improved the technical performance of LDCTM in this limited series. Further assessment of the safety and impact on diagnostic yield using larger patient cohorts is warranted.CVFCSF-venous fistulaIOCMiodinated contrast mediaLDCTMlateral decubitus CT myelography